Źródła do dziejów Uniwersytetu im. Adama Mickiewicza w Poznaniu. Protokoły posiedzeń Senatu Uniwersytetu Poznańskiego 1945. Tymczasowa Komisja Administracyjna Uniwersytetu Poznańskiego w Krakowie 27 I 1945 – 23 III 1945 - Sak, Monika; Domalanus, Anna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2025)
Kolejny tom wydawnictwa źródłowego stanowi uzupełnienie Protokołów posiedzeń Senatu Uniwersytetu Poznańskiego 1945. Opracowanie obejmuje materiały dotyczące działalności Tymczasowej Komisji Administracyjnej Uniwersytetu Poznańskiego i Akademii Handlowej od stycznia do marca 1945 r., a więc jeszcze w czasie trwania walk o Poznań. Pokazuje mało znany, a zarazem bardzo istotny epizod w dziejach Uniwersytetu Poznańskiego, i do tego znakomicie wpisuje się w obchody kolejnego jubileuszu Uniwersytetu im. Adama Mickiewicza w Poznaniu. Celem publikacji jest nie tylko ukazanie dziejów Uniwersytetu Poznańskiego w świetle źródeł archiwalnych, ale również zabezpieczenie najstarszych archiwaliów do dziejów UP dla przyszłych badań nad historią UAM oraz innych uniwersytetów poznańskich powstałych po II wojnie światowej na bazie wydziałów UP, takich jak: Uniwersytet Medyczny, Uniwersytet Przyrodniczy oraz Akademia Wychowania Fizycznego. The next volume of the source publication is a supplement to the Protocols of the Senate of the University of Poznań 1945. The study includes materials on the activities of the Temporary Administrative Commission of the University of Poznań and the Academy of Commerce from January to February 1945, while the fight for Poznań was still going on. It reveals a little-known yet very significant episode in the history of the University in Poznań, and that is why it perfectly fits in with the celebrations of the next Jubilee of Adam Mickiewicz University in Poznań. The aim of this publication is not only to present the history of the University of Poznań in the light of archival sources, but also to secure the oldest archival materials for future research on the history of AMU and other Poznań universities established after World War II out of University in Poznań departments, such as the University of Medical Sciences, the University of Life Sciences and the University of Physical Education.
Association of Polish Archivists, 2010-2014 member of the board of the Section on University and Research Institution Archives of the International Council of Archives. She has frequently represented the AMU Archives at meetings and conferences on archival issues. Awarded the "For merits for archival science" medal and the Prof. Stanislaw Nawrocki Prize for archivists. Privately, a passionate sailor.
Keywords: Akademia Handlowa; Tymczasowa Komisja Administracyjna; profesor; Jerzy Suszko; protokoły posiedzeń; rok 1945; Uniwersytet Poznański; Poznań University; Academy of Commerce; Temporary Administrative Commission; professor; minutes of meetings; 1945